Midterm Outcomes of a Synthetic Cartilage Implant for the First Metatarsophalangeal Joint in Advanced Hallux Rigidus. (April 2019) - Glazebrook, Mark; Blundell, Chris M.; O'Dowd, Dominic; Singh, Dishan; de Vries, Gwyneth; Le, Ian L. D.; Nielsen, Dominic; Pedersen, M. Elizabeth; Sakellariou, Anthony; Solan, Matthew; Wansbrough, Guy; Younger, Alastair S. E.; et al.
Background: A prospective, randomized, noninferiority clinical trial of synthetic cartilage implant hemiarthroplasty for hallux rigidus demonstrated functional outcomes and safety equivalent to first metatarsophalangeal (MTP) joint arthrodesis at 24 months. We prospectively assessed safety and efficacy outcomes for synthetic cartilage implant hemiarthroplasty at a minimum of 5 years. Methods: Of 135 eligible patients from the original trial, 112 (83.0%) were enrolled (mean age, 58.2 ± 8.8 years; 87 females). Pain visual analog scale (VAS), Foot and Ankle Ability Measure (FAAM) Activities of Daily Living (ADL), and FAAM Sports subscales were completed preoperatively and 2 and 5 years postoperatively. Great toe active dorsiflexion, weightbearing radiographs, secondary procedures, and safety parameters were also evaluated. Results: At 24 months, 14/152 (9.2%) patients had undergone implant removal and conversion to arthrodesis. In years 2 to 5, 9/119 (7.6%) patients underwent implant removal and conversion to arthrodesis. At mean 5.8 ± 0.7 (range, 4.4-8.0) years' follow-up, pain VAS, FAAM ADL, and FAAM Sports scores improved by 57.9 ± 18.6 points, 33.0 ± 17.6 points, and 47.9 ± 27.1 points, respectively, from baseline. Clinically significant changes in VAS pain, FAAM ADL, and FAAM Sports were reported by 103/106 (97.2%), 95/105 (90.5%), and 97/104 (93.3%) patients, respectively. Patient-reported outcomes at 24 months were maintained at 5.8 years in patients who were not revised. Active MTP joint peak dorsiflexion was maintained. Ninety-nine of 106 (93.4%) patients would have the procedure again. Conclusion: Clinical and safety outcomes for synthetic cartilage implant hemiarthroplasty observed at 2 years were maintained at 5.8 years. The implant remains a viable treatment option to decrease pain, improve function, and maintain motion for advanced hallux rigidus. Level of Evidence: Level IV, case series.